The Influence of Workload, Demographic Factors and Hardiness on Teachers’ Work Stress - Mohzana Mohzana; Muhamad Risal Tawil; Bayu Purbha Sakti; Akhmad Ramli; Fatimah Malini Lubis (Journal on Education, 2023)
The aim of this research was to assess the importance of the links between work strain faced by high school educators with resilience (devotion, command, and obstacles), work demands (physical demands and negative demands), and demographic characteristics (gender, years of experience, age, and job position). The research sample consisted of 217 teachers who were chosen randomly using the non-probability sampling technique of accidental sampling. Multiple regression analysis was utilized to examine the research hypothesis, while CFA (confirmatory factor analysis) was used to determine the consistency of the measuring tool. The results revealed that resilience, work demands, and demographic characteristics had a significant effect on teacher job strain. Based on the results of the minor hypothesis test, difficulties and attention had a significant impact on work strain. Work command, work demands (both physical and mental), gender, years of experience, age, and job position had no noticeable effect on work strain. The findings also indicated that only 21.6% of the variation in job strain was accounted for by all independent variables, while the remaining 78.4% was influenced by factors not addressed in this research.